Strategy Islamic Education in Indonesia Facing the Era of Society - Aris Fitriyani; Fauzi Fauzi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Islamic education today is facing challenges in welcoming the era of society 5.0. The challenge in the era of society 5.0 is to focus on increasing human resources because the era of society 5.0 places humans as the main component. In order to always exist and be able to face the era of society, the management of Islamic education is very important. This research is a literature study that interprets data by descriptive analysis. This study aims to see and examine the problems and challenges as well as the strategies used in the management of Islamic education to face the era of society 5.0. The results of the study show that the problems and challenges of Islamic education management related to human resources are still lacking in sufficient resources and there are main competencies that must be owned by individuals, namely:creativity, critical thinking, communication and collaboration.The Islamic education management strategy in facing the era of society 5.0 is by preparing human resources who have digital capabilities and are innovative and creative thinkers; change paradigm educational institutions; as well as preparing leaders of educational institutions who have a leadership spirit and are able to collaborate so that the demands for life skills in the 21st century are met.